Oxygen and radiogenic isotope constraints on the generation of coexisting silica-undersaturated and oversaturated felsic magmas of the Ditrau Alkaline Massif (Romania) - Odri, Agnes (Department of Geological Sciences, 2019)
The Ditrău Alkaline Massif (DAM) is a Mesozoic igneous complex (~200-230 Ma) was generated in a continental rift environment. This study has investigated the relationship between the silica-undersaturated and oversaturated Ditrău rocks based on oxygen, Sr, Nd and Pb isotope data. Different models have been proposed previously to explain the coexisting silica-undersaturated and oversaturated rocks in general: (1) both silicaundersaturated and oversaturated magmas evolve from the same mantle-derived, undersaturated melt, with the oversaturated rocks being produced by crustal assimilation (Foland et al., 1993); (2) both are derived from the same mantle source, but do not evolve from the same parental melt (Giret and Lameyre, 1985); (3) the sources are heterogeneous on a scale that allows undersaturated and oversaturated melts to be produced (Harris, 1995). The previous petrogenetic model of the DAM emphasises the importance of fractional crystallisation of a silica-undersaturated, mantle-derived magma (e.g. Morogan et al., 2000). The Ditrău rocks show variable initial 87Sr/86Sr ratios up to 0.72372, whereas ɛNdi values are from +5.5 to +0.8. High-temperature equilibrium O-isotope fractionations between minerals are generally preserved, but there was some sub-solidus O-isotope re-equilibration during slow cooling. Quartz, zircon and amphibole were used as a proxy for the magma δ18O values. The estimated magma δ18O values for Ditrău rocks are from 5.7 to 11.7‰. Isotope data are consistent with the involvement of both mantle and crustal sources in the formation of the DAM. The Nd and O isotope values of quartz monzonite can be explained by the subequal contribution of mantle-derived camptonite and the lower crustal partial melts generated by the intrusion of hot, mantle magmas. Both O and Nd isotope values show the dominantly mantle origin of hornblendites, diorites and nepheline syenites. The Nd and O isotope variations imply the involvement of 20-65% upper crustal melts into the re-injected camptonite magma to generate the Ditrău syenites, quartz syenites and granites. The isotope results of the DAM require the combination of the previously proposed models to explain its evolution and the relationship of the silica-undersaturated and oversaturated rocks.